Recent advances in cellulose and its derivatives for oilfield applications - Liu, Kun; Du, Haishun; Zheng, Ting; Liu, Huayu; Zhang, Meng; Zhang, Rui; Li, Haiming; Xie, Hongxiang; Zhang, Xinyu; Ma, Mingguo; Si, Chuanling (Carbohydrate polymers, 2021)
[Display omitted] •Properties and preparation of cellulose and its derivatives were introduced.•Application progress of cellulose and its derivatives in petroleum field was elaborated.•Prospects and challenges of cellulose and its derivatives used for oilfield chemicals was proposed. The purpose of this review is to summarize and discuss the recent developments in exploring cellulose and its derivatives in the applications of oilfield chemicals for petroleum drilling and exploiting. We begin with a brief introduction of cellulose and its common water-soluble derivatives, such as the carboxymethyl cellulose, hydroxyethyl cellulose, hydroxypropyl cellulose, hydroxypropyl methylcellulose, and amphoteric cellulose. Afterwards, the applications of cellulose derivatives in different petroleum exploitation processes, such as drilling, cementing, and fracturing, are set out in detail. Finally, the application perspectives and challenges of cellulose derivatives for oilfield applications are presented. This work demonstrates that cellulose derivatives have wide application prospects in oilfield industry in the future.